Respuesta :
To solve this for d, first distribute 6 into the values in the parentheses.
6(d+1)-2d=54
6d+6-2d=54
Then, combine like terms (add 6d+(-2d).
6d+6-2d=54
4d+6=54
Subtract 6 from both sides.
4d+6-6=54-6
4d=48
Divide both sides by 4 for d.
[tex]\frac{4d}{4}[/tex]=[tex]\frac{48}{4}[/tex]
d=12
Answer:
12
Step-by-step explanation:
6(d+1)−2d=54
Here, we have to find the value of d
multiply (d+1) by 6
6×d + 6×1 - 2 d= 54
6d + 6 - 2d= 54
Now subtract 2 d from 6d
6d- 2d +6= 54
4 d+ 6=54
Now, by using transposition method,
+ 6 will be transferred from L.H.S to -6 to R.H.S
4 d = 54- 6
4d= 48
Now, divide 48 by 4
d= 48÷ 4
d= 12
Hence, the value of d is 12
Hence, the correct answer is 12